Occupational Exposure to Poorly Soluble Low Toxicity Particles and Cardiac Disease: A Look at Carbon Black and Titanium Dioxide - McCunney, Robert J.; Yong, Mei; Warheit, David B.; Morfeld, Peter (Frontiers in Public Health, 2022)
Environmental particulate exposure and the potential risk to people with various types of cardiac diseases, most notably cardiovascular disease, have aroused scientific and regulatory interest worldwide. Epidemiological studies have shown associations between exposure to airborne environmental particulate matter (PM) and mortality from cardiovascular disease (CVD). The associations reported, however, are complex and may not involve a direct role for PM, since air pollutants are diverse and highly correlated. This study examines the potential role of occupational exposure to two types of particles, namely, manufactured carbon black (CB) and titanium dioxide (TiO2), on the risk of cardiovascular disease. To address the risk of cardiovascular disease from exposure to carbon black and titanium dioxide, as reflective of poorly soluble low toxicity particles, we reviewed the published cohort mortality studies of occupational exposure to carbon black and titanium dioxide. Mortality studies of carbon black have been conducted in the United States, Germany, and the United Kingdom. Five mortality studies related to workers involved in the manufacture of titanium dioxide in the United States and Europe have also been conducted. In addition, a meta-analysis of the three-carbon black mortality studies was performed. In the random-effects meta-analysis, full cohort meta-SMRs were 1.01 (95% confidence interval (CI): 0.79–1.29) for heart disease; 1.02 (95% CI: 0.80–1.30) for ischemic heart disease; and 1.08 (95% CI: 0.74–1.59) for acute myocardial infarction (AMI) mortality. A small but imprecise increased AMI mortality risk was suggested for cumulative exposure by a meta-HR = 1.10 per 100 mg/m3-years (95% CI: 0.92–1.31) but not for lugged exposures, that is, for recent exposures. Results of five cohort mortality studies of titanium dioxide workers in the United States and Europe showed no excess in all heart disease or cardiovascular disease. In the most recent study in the United States, an internal analysis, that is, within the cohort itself, with no lag time, showed that the exposure group 15–35 mg/m3-years yielded a significantly increased risk for heart disease; however, there was no evidence of increasing risk with increasing exposure for any of the exposure categories. In contrast to environmental studies, the results of cohort mortality studies do not demonstrate that airborne occupational exposure to carbon black and titanium dioxide particulates increases cardiovascular disease mortality. The lack of a relationship between carbon black and titanium dioxide and CVD mortality suggests that the associations reported in air pollution studies may not be driven by the particulate component.